Pediatric cements effect among ionomer Ketac Molar and the pediatric resin cement CROP faced to Streptococcus mutans - R A Figueroa-Banda (2017)
The objective of this investigation has been comparing the effect between two pediatric cements; which are restorative ionomer KETAC MOLAR and pediatric resin cement (CROP) and then take it to faced to Streptococcus mutants in order to see its reactions. These have the same feature to use like a restorative material in deciduous teeth. Additionally our method was the diffusion by profundity in petri plac and them we read results at 24 hours , 48 hours and 72 hours , large zones of inhibition observed in both pastes. The highest average zone of inhibition at 24 hours was for KETAC MOLAR (2.36mm) and the less was for CROP (2.10mm), at 48 hours the highest one was KETAC MOLAR (2.23mm)and the less one was CROP (2.21 mm) and finally at 72 hours the highest one again was KETAC MOLAR (2.34mm)and the less one was CROP (2.21mm). But they showed us no significant difference among two.